Personality Traits in Patients With Cirrhosis Are Different From Those of the General Population and Impact Likelihood of Liver Transplantation. Issue 2 (29th September 2022) - Thuluvath, Avesh J.; Siddiqui, Osama; Lai, Jennifer C.; Peipert, John; Levitsky, Josh; Daud, Amna; Mazumder, Nikhilesh R.; Flores, Anne-Marie; Borja-Cacho, Daniel; Caicedo, Juan C.; Loftus, Corinne; Wong, Randi; et al.
Abstract : Background: Personality traits influence clinical outcomes in chronic diseases, but their impact in cirrhosis is unknown. We studied the personality of patients with cirrhosis undergoing liver transplant (LT) evaluation and determined their correlation to clinical outcomes. Methods: A multicenter‚ prospective study of adult patients undergoing LT evaluation was performed from January 2018 to October 2019. The "Big Five" personality traits of conscientiousness, extraversion, openness, neuroticism, and agreeableness plus agency were assessed with the Midlife Development Inventory Personality Scale and compared with the general population. Frailty was assessed with the Liver Frailty Index. Results: Two hundred sixty-three LT candidates were enrolled. Twenty-four percent had hepatitis C virus, 25% nonalcoholic steatohepatitis, and 25% ethyl alcohol (mean model for end-stage liver disease = 15.7). Compared with the general population, LT candidates had higher openness (3.1 versus 2.9; P < 0.001), extraversion (3.2 versus 3.1; P < 0.001), agreeableness (3.5 versus 3.4; P = 0.04), agency (2.9 versus 2.6; P < 0.001), neuroticism (2.2 versus 2.1; P = 0.001), and lower conscientiousness (3.3 versus 3.4; P = 0.007). Patients with higher conscientiousness were more likely to receive an LT (HR = 2.76; P = 0.003). Conclusions: Personality traits in LT candidates differ significantly from the general population, with higher conscientiousness associated with a higher likelihood of receiving a transplant.